Retirement Patterns of Couples in Europe - Laura Hospido; Gema Zamarro (Institute for the Study of Labor (IZA), 2014)
In this paper we study the retirement patterns of couples in a multi-country setting using data from the Survey of Health, Aging and Retirement in Europe. In particular we test whether women's (men's) transitions out of the labor force are directly related to the actual realization of their husbands' (wives') transition, using the institutional variation in country-specific early and full statutory retirement ages to instrument the latter. Exploiting the discontinuities in retirement behavior across countries, we find a significative joint retirement effect for women of 21 percentage points. For men, the estimated effect is insignificant. Our empirical strategy allows us to give a causal interpretation to the effect we estimate. In addition, this effect has important implications for policy analysis.
Keywords: J26; D10; C21; 330; joint retirement; social security incentives